An Attractive Choice: Education Researchers’ Use of Participatory Methodology - Ebersohn, Liesel; Ferreira, Ronel; Beukes, Janna (South African Journal of Higher Education, 2016)
Participatory methodologies are often favoured in education research. This study aimed to determine collaborative partnership trends between education researchers and teachers in order to understand the use of participatory theory and practice in education studies. Seven symposium presentations by education scholars from various higher education institutions were analysed using trend analysis from a community of practice theoretical framework. It emerged that participatory methodology denotes various characteristics which indicate favourable use by education researchers. Partnerships between education researchers and teachers share common goals, are contextual in nature, have a process-oriented emphasis and foreground knowledge exchange and the development of knowledge networks. In addition, collaborative partnerships between education researchers and teachers appear to be directed by an overarching philosophy of ‘care’.